Nasalis típusú extranodalis natural killer T-sejtes lymphoma hazai előfordulása és kezelésével szerzett tapasztalatok - Bakos Annamária; Szomor Árpád; Schneider Tamás; Miltényi Zsófia; Marton Imelda; Borbényi Zita; Pammer Judit; Krenács László; Bagdi Enikő; Piukovics Klára (2017)
INTRODUCTION: Extranodal natural killer/T (NK/T) cell lymphoma, nasal type (ENKTL) represents a rare subtype of T-cell lymphomas with aggressive clinical behavior according to WHO 2016 classification. AIM: ENKTL has distinctive geographic distribution with higher incidence in Asia and Latin America (10% of all non-Hodgkin lymphoma cases), than in Europe and North America (<1%). ENKTL tipically origins from nasopharynx and upper aerodigestive tract. Anthracycline-based chemotherapy regimens are largely ineffective in the treatment of ENKTL. METHOD: Our aims were to evaluate the incidence and treatment strategies of ENKTL patients in Hungarian Haematological Centres between 2003 and 2015. Altogether 20 patients with ENKTL were treated in the 4 haematological hospitals (male:female ratio 12:8, with median 49.5 years of age). RESULTS: Ten patients had localized (stage I-II) disease at the time of the diagnosis. Seventeen patients were treated with chemotherapy (11/CHOP, CHOP-like, 2/HyperCVAD, 1/ProMACECytaBom, 1/SMILE, 2/others), which was completed with involved-field radiation therapy (IFRT) (40-46 Gy) in 6 cases were used. After first-line therapy 9 patients achieved complete remission (CR), 3 patients had partial remission (PR), 3 patients had progressive disease (PD), and 2 patients had stable disease (SD). Median follow-up was 32 (3-113) months. Five patients received second-line therapy for progressive or recurrent disease [2/DHAP, 1/VIM, 1/HyperCVAD, 1/ProMACECytaBom]. None of the patients achieved CR after second-line therapy. Two patients have undergone autologous hematopoietic stem cell transplantation (HSCT) after the first CR. CONCLUSION: ENKTL treatment is more effective with nonanthracycline-containing regimens. L-asparaginase containing chemotherapy and concurrent or sequential chemo-radiotherapy improves survival and CR rates. Orv Hetil. 2017; 158(41): 1635-1641.